Developing “SiGaya” Web-Based Interactive Learning Media Using Google Sites : Effect on Motivation and Science Learning Outcome in Primary Education - Rosalia Eka Lusiana; Achmad Buchori; Harjito (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop a web-based interactive learning media called “SiGaya” using Google Sites to enhance elementary school students’ motivation and learning outcomes in science. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The SiGaya media was designed with interactive features such as videos, quizzes, and games to support engaging and effective learning experiences. The participants consisted of 25 fourth-grade students from an elementary school in Semarang, Indonesia. Data were collected through observations, interviews, questionnaires, and achievement tests. The data were analyzed using descriptive quantitative analysis, descriptive qualitative analysis, and inferential statistics. The results show that the content expert validation of the SiGaya media achieved a score of 94%, categorized as very good. Meanwhile, the media expert validation obtained a score of 88%, which is also categorized as very good. Furthermore, the effectiveness test revealed an N-Gain score of 0.71 (71%), indicating a high level of improvement in students’ learning outcomes. Statistical analysis also demonstrated a significant difference between the pretest and posttest scores (p < 0.05). Therefore, the findings suggest that SiGaya is a valid, practical, and effective web-based learning medium that can enhance students’ motivation and learning outcomes in elementary science education. This study contributes to the integration of digital learning innovations in primary education and offers a scalable model for technology-enhanced science learning.